2014
DOI: 10.1002/jbm.a.35114
|View full text |Cite
|
Sign up to set email alerts
|

Critical size defect regeneration by rhPTH-collagen membrane as a new tissue engineering tool

Abstract: Recombinant Human Parathyroid Hormone (rhPTH 1-34) administration is an effective treatment to improve bone mass in osteoporosis. The aim of this study was to develop a Tissue Engeenering Tool for bone regeneration. We evaluated the efficacy of a freeze dried rhPTH membrane in calvarial critical size defect (CSD). Forty-four Wistar female rats (body weight 150 ± 50 g) with CSD (5 mm) were divided into four groups: group 1: rhPTH membrane (rhPTHm); group 2: atelocollagen membrane (Cm); group 3: rhPTH and ateloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…With PTHdP loaded on implants, the PTHdP-10/CH/TBC and PTHdP-100/CH/TBC groups both revealed a remarkably stronger ability to stimulate peri-implant new bone formation and induce guided bone regeneration into implants interspace for the implantation periods used. These results were consistent with previous studies, which demonstrated enhanced osseointegration and bone-defect regeneration was obtained by local application of PTH. ,, In the present study, as PTHdP/CH/TBC implants were applied in vivo, the local concentration of released PTHdP for the first few days could be conceivably high because of the initial uncontrolled and rapid PTHdP release. As observed in vitro, this rapid release resulted in significant inhibitory effects on osteogenesis actions for MC3T3-E1 cell culture.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…With PTHdP loaded on implants, the PTHdP-10/CH/TBC and PTHdP-100/CH/TBC groups both revealed a remarkably stronger ability to stimulate peri-implant new bone formation and induce guided bone regeneration into implants interspace for the implantation periods used. These results were consistent with previous studies, which demonstrated enhanced osseointegration and bone-defect regeneration was obtained by local application of PTH. ,, In the present study, as PTHdP/CH/TBC implants were applied in vivo, the local concentration of released PTHdP for the first few days could be conceivably high because of the initial uncontrolled and rapid PTHdP release. As observed in vitro, this rapid release resulted in significant inhibitory effects on osteogenesis actions for MC3T3-E1 cell culture.…”
Section: Resultssupporting
confidence: 93%
“…Generally, prolonged and high doses of exposure to PTH(1–34) leads to increased bone resorption, yet intermittent doses of higher amounts or infusion of low doses results in bone formation . In addition to its prevalent application in treating osteoporosis, intermittent administration of PTH(1–34) has been found to significantly stimulate bone-defect regeneration, , making it available to expand the application of PTH(1–34) to a bone graft procedure. , However, the inconvenience of daily injection, low bioavailability with short lasting duration, and even potential safety risk of systemic exposure severely hinder the broader application of PTH(1–34). , To overcome these disadvantages, localized and controlled delivery of PTH(1–34) via high-affinity immobilization on drug-delivery vehicles, such as PLGA microspheres, fibrin polymer, biomimetic CaP coating, polyethylene glycol-based matrix, and atelocollagen membrane, have been explored. As these studies concluded, a proper local delivery system could be effective to maintain the bioactivity of PTH(1–34) and achieve local bone healing without the potential problems caused by systemic PTH exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report demonstrated that BMP2 plays an important role in host dura mater stimulation of human ASC osteogenesis in the context of calvarial bone healing [37]. Implant of recombinant human parathyroid hormone and atelocollagen I effectively regenerated critical-size Wistar female rat calvarial defects compared to use of atelocollagen I alone [38]. …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Accordingly, metallic, ceramic, or polymeric scaffolds, alone or in combination with cells, can be satisfactorily employed to promote bone regeneration and facilitate the reconstruction of critical size defects. [3][4][5][6][7][8] Ideally, the scaffolds used for bone tissue engineering should have a three-dimensional, highly porous structure with an interconnected pore network. All these geometrical features facilitate cell migration and tissue ingrowth and are important for neovascularization, affecting directly the flow of nutrients and metabolic waste.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the drawbacks associated to autografts and allograft for bone regeneration, such as scarcity of healthy tissue or possible rejection of the implanted grafts, tissue engineering is presented as a promising alternative for the reconstruction of critical size bone defects . Accordingly, metallic, ceramic, or polymeric scaffolds, alone or in combination with cells, can be satisfactorily employed to promote bone regeneration and facilitate the reconstruction of critical size defects …”
Section: Introductionmentioning
confidence: 99%